New Frontiers in Sustainable Geotechnics - Jastrzębska, Małgorzata; Kazimierowicz-Frankowska, Krystyna; Chiaro, Gabriele; Rybak, Jaroslaw (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
With increasing awareness about environmental sustainability issues, the geotechnical engineering community is in search of sustainable materials, innovative applications and ground improvement technologies which are resilient to climate change, involve low carbon emissions, are ecologically friendly and affordable, yet effective. As such, this reprint brings together 18 novel contributions providing the state-of-the-art in "Sustainable Geotechnics" with special focus on the reuse and recycling of waste materials in geotechnical applications as well as sustainable design, construction, and monitoring of the performance of geostructures. This reprint may be of particular interest to geotechnical professional engineers and researchers who are facing the challenging task of increasing the sustainability and resiliency of geotechnical assets and infrastructures.